Perubahan Undang-Undang Dasar (Pemahaman Tentang Arti Perubahan, Tatacara Perubahan, Kajian Kritis Terhadap Amandemen UUD 1945) - Wilma Silalahi; Marsalina Susana (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2025)
In an ideal order, the constitution of a country must be in line with the values of constitutionalism. The development of the constitution in Indonesia can be grouped into several periods. The first period of the 1945 Constitution, the period of the two parties to the 1949 RIS, the third period according to the 1950 Provisional Constitution, the fourth period with the 1945 Constitution and its explanations. After that the 1945 Constitution was amended successively in 1999, 2000, 2001, 2002 by using a text that was ready from July 5, 1959 as a standard for making changes outside the text which was then used as an inseparable attachment to the manuscript of the 1945 Constitution. The development of the constitution in Indonesia which has been established since August 18, 1945. The approach used is normative juridical, while the data source is secondary data, the analysis uses a qualitative description. The results obtained show that the constitution in Indonesia has undergone several changes, including the 1945 Constitution, the RIS UUDS, the 1950 UUDS and back again to the 1945 Constitution until it has been amended 4 (four) times and has worked until now. Changes in the Indonesian constitution which were caused by external factors and internal factors as well as the existing political and legal conditions had an impact on the changing constitutional system in Indonesia.